RUNX3 Inhibits the Invasion and Metastasis of Human Colon Cancer HT-29 Cells by Upregulating MMP-2/9. (27th February 2020) - Xue, Jun; Wu, Xueliang; Qu, Ming; Guo, Fei; Han, Lei; Sun, Guangyuan; Yuan, Zelong; Fan, Shuang; Li, Tian
Abstract : Objective . To investigate the effect of Runt-associated transcription factor 3 (RUNX3) on the invasion and metastasis of human colon cancer HT-29 cells and to preliminarily explore the mechanism of its anticancer effect. Methods . The RUNX3 plasmid vector was transfected into human colon cancer HT-29 cells by liposome-mediated transfection, while the empty vector and the blank group were used as the control group. After Geneticin (G418) screening, HT-29 cells with stable expression of RUNX3 gene were obtained. The expressions of mRNA and proteins of RUNX3 and metalloproteinases (MMP)-2/9 were detected by reverse transcription-polymerase chain reaction (RT-PCR) and western blot. Cell proliferation was determined by MTT assay. The effect of RUNX3 on invasion and metastasis of HT-29 cells was evaluated by scratch injury assay, Transwell chamber, and Matrigel invasion model. Results . RUNX3 was expressed stably in HT-29 cells after transfection. The expressions of RUNX3 mRNA and proteins in the experimental group were significantly higher than those in the blank/empty vector groups. Meanwhile, the expressions of MMP-2/9 mRNA and proteins in the observation group were significantly lower than those in the blank group and the empty vector group. The proliferation and migration ability in the experimental group was significantly lower than blank/empty vector groups from the third day. Transwell chamber experiment and Matrigel invasion assay showed that the number of Transwell cells was decreased significantly than blank/empty vector groups, but no difference was found between the blank group and the empty vector group. Conclusion . RUNX3 can inhibit the invasion and metastasis of human colon cancer HT-29 cells, and the mechanism may be related to decreased expression of MMP-2 and MMP-9.